The Employment Level of Teaching Technology from the First Three Grades Teachers who enrolled The Reading and Mathematics Initiative in Zarqa first region in Jordan - Odeili, Samer Abdullah Mustafa (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the level of the first three grades teachers who joined the Reading And Mathematics Initiative in employment the teaching technology in government schools of the education directorate in the Zarqa region. To achieve the study aims the researcher used the descriptive approach, and the questionnaire was the tool which applied on a sample of (60) male teachers and (226) female teachers. The result showed that the level of degree of effectiveness of the Reading and Mathematics Initiative in developing the use of Educational Technology was moderated with (3.32) score, the result also showed that there were significant differences refers to years of experiences in favor of (11 years and more) and the teachers’ qualification in favor of (master degree and more).